Corrections to "Comprehensive Analysis of Design and Performance Evaluation Methodologies for a High-Resolution Read-Out IC With Ultralow 1/ f Corner for DC Measurement Applications" - Kang, Junho; Han, Woosol; Kim, Suhwan; Jun, Jaehoon (IEEE transactions on instrumentation and measurement, 2025)
Presents corrections to the paper, (Corrections to "Comprehensive Analysis of Design and Performance Evaluation Methodologies for a High-Resolution Read-Out IC With Ultralow 1/ f Corner for DC Measurement Applications").